Low-Rise Building Wind Load Provisions - Chiu, Gregory L.F.; Perry, Dale C. (Engineering Journal, 1997)
The National Standard ASCE 7 was revised and published in January 1996 following many years of study by the Wind Loads Subcommittee of ASCE 7. Contained for the first time are a complete set of provisions for assessing wind loads for the design of low-rise buildings. The provisions are based, for the most part, on the research conducted at the University of Western Ontario during the late 1970s (funded, in part by MBMA), the following extensive research reported from Concordia University, and the very recent activity at the University of Western Ontario supported by the timber industry (as yet not subject to proper peer review). The new low-rise provisions reflect rather substantial reductions in loading requirements for some design applications. The object of this communication is to briefly review the changes incorporated in ASCE 7-95 for Buildings of All Heights, Other Structures and Low-rise Buildings and compare the new wind load provisions with those contained in other codes and standards currently in use. The troublesome items that may impede acceptance of the new Standard and should be addressed in the future are cited.